PERSEPSI DAN SIKAP MASYARAKAT TERHADAP KONSERVASI EKOSISTEM MANGROVE DI PULAU TANAKEKE SULAWESI SELATAN - heru setiawan (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
People’s perception and attitude towards mangrove conservation determine the success of mangrove rehabilitation. This study examines the level of people’s perception and attitude toward mangrove conservation at Tanakeke Island. Data collection was conducted by field observation, interview, questionnaire and study literature. The overall number of respondents was 124 people spread proportionally according to the number of family in each village. The level of perception and attitude were obtained by using scoring techniques and factors that influence the level of perception and attitude, then were analyzed by using multiple linear regression. The results showed that based on the community perception, mangrove forests can provide variety of benefit to support their life, both ecology and economically. Level of people’s perception was included in the medium category with 41.1% respondents, 40.3% at lower category and higher category with 18.5% . Levels of public attitudes were dominated at low level by 65.3% respondents, medium category with 25.8% and high category with 8.9%. There were three independent variables that significantly influence the level of public perception on mangrove conservation, namely residence location (villages), education level and participation in mangrove rehabilitation. Independent factor that significantly influence the level of people's attitudes, namely participation in mangrove rehabilitation.